THE EFFECT OF MOTIVATION ON EMPLOYEE SATISFACTION PT COCA COLA OFFICIAL DISTRIBUTOR PEKANBARU - Bobby Kurniawan; Zulher Zulher; Azhari Azhari (Jurnal Riset Manajemen Indonesia, 2021)
A person with a high level of satisfaction has high positive feelings about his job. Satisfaction is determined by several factors, and one of them is work motivation. This study aims to determine the effect of motivation (X) on Job Satisfaction of employees of PT Coca Cola Pekanbaru (Y). This research is a quantitative study using simple linear regression analysis. The t test results show that the significance value is 0.000 <0.05, which means that motivation has a significant effect on job satisfaction of employees of PT Coca Cola Official Pekanbaru. The relationship between motivation and employee job satisfaction is very strong.